CONSIDERATIONS REGARDING THE CONSTITUTIONAL PROTECTION OF SEVERAL SOCIAL RIGHTS - Belea, Simion (International Journal of Legal and Social Order, 2025)
The protection of social rights, particularly for vulnerable individuals, represents a fundamental aspect of the contemporary constitutional law across all states. Social rights are among the human fundamental rights and entail the state’s obligation to eliminate economic and social inequalities to ensure the citizens well-being. This paper aims at analysing the protection of social rights at the international level, as well as the European Union as a supranational legal source. In its final section, the paper examines the protection of these rights at the national level, with reference to specific articles of the Romanian Constitution that safeguard citizens’ social rights.